2017
DOI: 10.1093/molbev/msx190
|View full text |Cite
|
Sign up to set email alerts
|

Global Dosage Compensation Is Ubiquitous in Lepidoptera, but Counteracted by the Masculinization of the Z Chromosome

Abstract: While chromosome-wide dosage compensation of the X chromosome has been found in many species, studies in ZW clades have indicated that compensation of the Z is more localized and/or incomplete. In the ZW Lepidoptera, some species show complete compensation of the Z chromosome, while others lack full equalization, but what drives these inconsistencies is unclear. Here, we compare patterns of male and female gene expression on the Z chromosome of two closely related butterfly species, Papilio xuthus and Papilio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 100 publications
(137 reference statements)
5
54
0
Order By: Relevance
“…It has been recently shown that, like in other taxa, sex-biased genes can experience rapid turnovers in butterflies (e.g., Papilio) (Huylmans et al, 2017 (Kozak et al, 2015) compared to 35MYA for P. xuthus and P. machaon (Zakharov, Caterino, & Sperling, 2004). Regardless, any gene that is sex biased in H. erato but not in H. melpomene is categorized as unbiased in our data.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…It has been recently shown that, like in other taxa, sex-biased genes can experience rapid turnovers in butterflies (e.g., Papilio) (Huylmans et al, 2017 (Kozak et al, 2015) compared to 35MYA for P. xuthus and P. machaon (Zakharov, Caterino, & Sperling, 2004). Regardless, any gene that is sex biased in H. erato but not in H. melpomene is categorized as unbiased in our data.…”
Section: Discussionsupporting
confidence: 42%
“…It has been recently shown that, like in other taxa, sex‐biased genes can experience rapid turnovers in butterflies (e.g., Papilio ) (Huylmans et al., ). Consequently, it is possible for H. melpomene and H. erato to have different sex‐biased genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have spawned both theoretical and empirical interest in sex chromosomes as models to study the consequences of recombination suppression and associated processes (Bachtrog, 2008;Charlesworth & Charlesworth, 2000;Corcoran et al, 2016;Doorn & Kirkpatrick, 2007; L. Gu, Walters, & Knipple, 2017;Huylmans, Macon, & Vicoso, 2017;Muyle et al, 2012;Peichel et al, 2004) . More recent studies investigating sex chromosomes in insects (Blackmon, Ross, & Bachtrog, 2017) , non-avian reptilia (Modi & Crews, 2005) , amphibians (Miura, 2017) , and fishes (Kikuchi & Hamaguchi, 2013) have found many homomorphic sex chromosomes displaying varying levels of differentiation, with the extreme case of a sex locus restricted to allelic variation of a single nucleotide as reported in the Japanese pufferfish (Kamiya et al, 2012) .…”
Section: Introductionmentioning
confidence: 99%
“…In Heliconius males expression of Z genes is reduced below autosomal levels, but this dosage compensation mechanism is imperfect, with males showing increased expression relative to females on the Z chromosome (Walters et al ., 2015). However, alternative processes, such as the masculinization of the Z chromosome, may explain the apparent lack of complete dosage compensation (Gu & Walters, 2017, Huylmans et al . 2017).…”
Section: Discussionmentioning
confidence: 99%